Effects of night duty events on blood pressure and autonomic modulation in physicians. Issue 8 (20th May 2018) - Lee, Hsiu‐Hao; Chen, Bing‐Yu; Pan, Shih‐Chun; Lo, Shih‐Hsiang; Chen, Pau‐Chung; Guo, Yue Leon
Abstract : Background: The dynamic effects of duty events on the blood pressure (BP) and heart rate variability (HRV) of physicians on duty are unknown. Methods: A study was conducted among 12 physicians on night duty. BP and HRV with and without the effect of a duty event were compared. The risk of higher BP and impaired HRV after a phone call were calculated. Results: Physicians had higher mean BP (122.4 ± 11.1; 76.9 ± 7.1 mmHg) within 30 min after a phone calls than without a phone call (113.5 ± 5.3; 69.0 ± 3.8) and higher sympathetic tone (low frequency normalized units (LFnu) 68.5 ± 8.9; high frequency normalized units (HFnu) 27.7 ± 8.7) within 10 min of a phone call than without a phone call (62.9 ± 8.51; 33.5 ± 8.4). Elevated BP and sympathetic tone recovered to baseline levels 30 min after a phone call. Conclusions: Among physicians on night duty, sympathetic tone and BP might be elevated by clinical events, and these effects last for 30 min.